Processing Mixture Of Polyethylene Terephthalate (PET) Plastic Waste and Oil Palm Empty Fruit Bunches by The Cracking Method : PENGOLAHAN CAMPURAN SAMPAH PLASTIK POLYETYLENE TEREPHTHALATE (PET) DAN TANDAN KOSONG KELAPA SAWIT DENGAN METODE PERENGKAHAN - Rahmawati Rahmawati; Hutwan Syarifuddin; Nazarudin Nazarudin (Jurnal Pembangunan Berkelanjutan, 2022)
The composition of waste in Jambi City is dominated by plantation waste and plastic waste, if not managed properly, it can have a negative impact on the environment. There is a need for alternatives to processing plastic waste and plantation waste, one of which is the catalytic cracking process to produce alternative fuels. The catalyst used is petroleum refining industry waste that can be reused. This study aims to analyze the characteristics of FCC (Fluid Catalytic Cracking) catalysts and the effect of the ratio of Polyethylene Terephthalate (PET) plastic waste and Oil Palm Empty Fruit Bunches (OPEFB) on the percentage of products produced. The experimental design used in this study was a Complete Randomized Design (RAL) with variations in the ratio of PET plastic : oil palm empty fruit bunches, namely 1:0, 1:1, 1:2, and 1:3 at a temperature of 450°C and a time of 40 minutes. The results of the analysis showed that spent FCC catalysts were predicted to contain zeolite Y (rich in silica) which had a pore structure of different sizes, while the ratio of PET plastic waste and oil palm empty fruit bunches had a significant effect on the percentage of cracking liquid, charcoal, and gas. The 1:3 ratio treatment resulted in the highest percentage of cracking oil and charcoal at 27.85% and 34.41%. While the percentage of gas was the highest in the 1:0 treatment, which was 82.12%. Keywords: catalytic cracking, polyethylene terephthalate, plastic waste, biomass, empty bunches of palm oil, catalyst spent FCC